Investigating Ottoman Press Censorship in the Eastern Mediterranean Through Conceptual History: The Peculiar Use of ‘Incident’ (ḥāditha) - Grallert, Till (Die Welt des Islams, 2026)
This paper re-evaluates the history of Ottoman censorship through the lens of conceptual history, focusing on how the periodical press of Damascus and Beirut reported incidents of violence between 1875 and 1914. I argue that well into the twentieth century, the Ottoman state had insufficient power to comprehensively enforce censorship. Instead, the press and the state were interdependent and shared the belief in a modernising project with the ever-expanding state at its core. The press largely understood its role as serving society as it moved along this path to progress and prosperity. Thus, we encounter deeply entrenched editorial tactics, epitomised by the reference to generic "incidents", to deal with the tension between violence as a quotidian phenomenon and its very occurrence being perceived as a fundamental challenge to the social contract. Analysing the tactics used to delegitimise acts of violence and their perpetrators, the paper establishes an ontology and a topography of the discourse on violence in the late Ottoman Eastern Mediterranean.